2011
DOI: 10.1111/j.1749-6632.2010.05907.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of STAT5 in the development, function, and transformation of B and T lymphocytes

Abstract: The transcription factor signal transducer and activator of transcription 5 (STAT5) is activated by a number of cytokine and growth hormone receptors and plays a key role in the development and function of many organ systems. In this review, we focus on recent discoveries about the role of STAT5 in the development and function of B and T lymphocytes. Of particular interest is the growing appreciation for the function of STAT5 as a transcriptional repressor. Finally, we discuss recent discoveries about the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 97 publications
(224 reference statements)
1
24
0
Order By: Relevance
“…Interestingly, STAT5 over-activation and PAX5 haplo-insufficiency have been described as synergistic players to initiate ALL [28, 32]. In the present study we demonstrated that both these aberrancies are not only necessary to drive leukemia, but they are a direct consequence of the expression of the PAX5 fusion protein, which can a) repress the activity of endogenous PAX5 [11] and b) activate STAT5 through LCK (Figure 6).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, STAT5 over-activation and PAX5 haplo-insufficiency have been described as synergistic players to initiate ALL [28, 32]. In the present study we demonstrated that both these aberrancies are not only necessary to drive leukemia, but they are a direct consequence of the expression of the PAX5 fusion protein, which can a) repress the activity of endogenous PAX5 [11] and b) activate STAT5 through LCK (Figure 6).…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, we demonstrated by phosphoflow analysis that PAX5/ETV6 transduced cells showed increased Stat5 phosphorylation, and the up-regulation of two downstream targets cMyc and Ccnd2 , known to have a role in cell cycle progression and malignant transformation [22, 28, 29]. We also demonstrated that IL7Rα (CD127) was expressed at the same level both in PAX5/ETV6 and MIGR-GFP cells, thus suggesting that increased Stat5 phosphorylation was independent from classical IL7R signaling cascade [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found aberrantly activated in leukemia and lymphoma as well as solid cancers as breast and prostate cancer (reviewed in refs. [43][44][45]. In this light, it is surprising how little is known about the function of STAT5 and its downstream targets in CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated Stat5 activity in the hematopoietic system is associated with the development of Hodgkin's lymphoma and Burkett's lymphoma in humans [19] and, via the kinase BCR–ABL, with myeloid leukemia [20]. In the mammary gland, studies in transgenic animal models have indicated that deregulated STAT5 levels and activity represent a genuine risk factor for breast cancer [21].…”
Section: Introductionmentioning
confidence: 99%